Progressive Antithrombin and Fibrinogen The Antithrombin Time According to Innerfield and its Relation to Acute Pancreatitis - Greep, J. M; Loeliger, E. A; Roos, J (Thrombosis and Haemostasis, 1961)
Innerfield’s method of determining antithrombin III using plasma “defibrinated” by thrombin is submitted to criticsm. This method proves to involve insufficient defibrination: the higher the fibrinogen concentration of the plasma to be tested, the larger the fibrinogen remnant after “defibrination”. The residual fibrinogen interferes in the determinations of antithrombin III, as fibrin (antithrombin I) adsorbes thrombin; an increase in antithrombin III activity is suggested. This becomes manifest in all conditions associated with hyperfibrinogenaemia, including acute pancreatitis.